3D hierarchical SnO2@Ni(OH)2 core–shell nanowire arrays on carbon cloth for energy storage application. Issue 18 (14th May 2015) - Ke, Qingqing; Guan, Cao; Zheng, Minrui; Hu, Yating; Ho, Kuan-hung; Wang, John
<x xml:space="preserve">Abstract</x> A judicious combination of conducting materials with selected transition metal hydroxides to form core–shell nanostructures has attracted great attention owing to the underlying synergistic effect for energy storage.